Electrical behavior of ethylene carbonate-plasticized cellulose biopolymer electrolyte films - Ahmad Sohaimy M.I.H.; Ahmad Fauzi M.J.; Mohamad Isa M.I.N. (Malaysian Institute of Chemistry, 2024)
Indexed by SCOPUS/MYCITE